Culture, Values and Integrity in Contemporary Society - Small , Michael Willoughby (Journal of Law and Governance, 2014)
Comments in the Australian press and the media have suggested that all is not well within certain sections of Australian society. This view was publicised by comments of the Chief of the Australian Army, who had stated in vigorous terms that he intends to change the culture in the Army. Changing the culture of any organisation is difficult, slow and time consuming, and so in an endeavour to facilitate this process, it is argued that some thought might be given to studying some of the classical writers who were faced with similar problems thus illustrating the relevance and timeliness of their ideas.